Implementation of the Pancasila Student Profile Strengthening Project in Inclusive Schools - Librayanti, Ni Kadek Gita; Asril, Nice Maylani (Jurnal Pedagogi dan Pembelajaran, 2024)
Facts on the ground show that children are less motivated. Lack of motivation in children is caused by children finding it difficult to implement the Pancasila student profile strengthening project. This study aims to prove the implementation of the Pancasila student profile strengthening project in the independent curriculum in schools that provide inclusive education. This study is a type of qualitative research with a case study approach. The subjects of this study were 1 head of the Foundation, and 1 teacher for grades I and II each. The data collection methods used were observation and interviews. The data collection instruments were observation guidelines and interview guidelines. The data analysis technique used was interactive model qualitative data analysis. The results of this study are that the implementation of P5 activities for inclusive schools can be carried out through 3 stages. So it can be concluded that the planning, implementation, and evaluation of the Pancasila student profile strengthening project are running according to the stages of its development and from the project activities, the planning, implementation, and evaluation processes occur in children. The latest results in this study can have implications for its use as a reference or reading material for consideration in making policies related to the Pancasila Student Profile Strengthening Project, especially for early childhood, especially with children with special needs.